Completion of the Maternal Health Care Continuum-Barriers and Facilitators Among Pregnant Women in Jimma Zone, Southwest Ethiopia: A Prospective Study - Sena Belina Kitila; Garumma Tolu Feyissa; Muluemebet Abera Wordofa (SAGE Publishing, 2023)
Background: Continuum of care (CoC) for Maternal Health Care (MHC) is a key strategy aimed at saving lives and promoting the well-being of women and newborns. To achieve the global targets for reducing maternal and newborn mortality, it is preferable to ensure the completion of key care stages (Antenatal, Institutional Delivery, and Postnatal) rather than fragmented care. Therefore, investigating the determinants of CoC completion for MHC is imperative for recommending schemes and designing strategies. Objective: To assess the determinants influencing completion of the maternal healthcare continuum among pregnant women in Jimma Zone, Southwest Ethiopia. Methods and Materials: A community-based prospective study was conducted from July 2020 to June 2021 among 1065 pregnant women from randomly selected woredas in Jimma Zone. The data were collected, entered using Epi-data and analyzed with SPSS software. Binary logistic regression was used to select candidate variables for multivariate analysis. Multivariate analysis was performed to identify associations between the dependent and independent factors. Principal Component Analysis (PCA) was used to determine the socioeconomic index. Results: The overall completion rate was 16.1% (CI, 13.8%-18.5%), with significant dropouts observed between the first and the fourth ANC. Factors associated with the completion of MHC included the women's residence (AOR: 1.73 95% CI: 1.07, 2.81), educational status of their partners (AOR: 5.60 95% CI: 2.40, 13.08), women's occupation (AOR: 2.57 95% CI: 1.28, 5.16), knowledge of ANC (AOR: 7.64 95% CI: 4.03, 14.48), knowledge of PNC (AOR: 4.88 95% CI: 3.21, 7.42), service provided during ANC contacts (AOR: 3.39 95% CI: 1.94, 5.93), parity (AOR: 1.86 95% CI: 1.11, 3.12), time of booking for ANC (AOR: 2.10 95% CI: 1.45, 3.03), and nature of care (AOR: 2.03 95% CI: 1.07, 3.82). Additionally, factors such as topography, distance, lack of transportation, facility closeness, and indirect costs were associated with the completion for MHC. Conclusion and Recommendations: The completion rate of CoC for MHC remains low. Factors influencing completion include women's residence, partners' educational status, women's occupation, services provided during ANC, history of PNC use, parity, time of booking for ANC, knowledge of ANC and PNC, and nature of care. To address this, strategies should focus on empowering women economically, improving knowledge of ANC and PNC, enhancing the capacity of health facilities to provide comprehensive ANC services, and making the service delivery more supportive. Further research is recommended to explore the impact of CoC for MHC on birth outcomes.